2014
DOI: 10.1136/bjophthalmol-2014-305149
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and adverse events of aflibercept, ranibizumab and bevacizumab in age-related macular degeneration: a trade-off analysis

Abstract: The study revealed only a modest superiority of aflibercept 2 mg and ranibizumab 0.5 mg over other formulations and dosages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 25 publications
0
74
0
3
Order By: Relevance
“…Because the intravitreal injection of anti-VEGF drugs has also been revealed by meta-analyses to increase the risk of systemic thrombotic events [11,12], the results of our present study should not be interpreted as indicating that intravitreal injections of anti-VEGF drugs are safe for systemic thrombotic events. Ophthalmologists must carefully exclude patients with preexisting thrombotic diseases and patients at high risk for thrombotic events when they consider administering intravitreal injections of any type of anti-VEGF drugs.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Because the intravitreal injection of anti-VEGF drugs has also been revealed by meta-analyses to increase the risk of systemic thrombotic events [11,12], the results of our present study should not be interpreted as indicating that intravitreal injections of anti-VEGF drugs are safe for systemic thrombotic events. Ophthalmologists must carefully exclude patients with preexisting thrombotic diseases and patients at high risk for thrombotic events when they consider administering intravitreal injections of any type of anti-VEGF drugs.…”
Section: Discussionmentioning
confidence: 51%
“…Several meta-analyses of exudative AMD studies revealed that, compared to the placebo group, the number of serious systemic vascular side effects was higher not only in IVA-treated patients but also in those treated with IVR [11,12]. However, it remains unclear whether an intravitreal injection of an anti-VEGF drug exacerbates large-vessel arteriosclerosis, which is a risk factor for systemic thrombotic events.…”
Section: Introductionmentioning
confidence: 99%
“…11,18,19 These components enable aflibercept to have much higher binding capacity than the others. [17][18][19][20] It is hypothesized to enable a more persistent and longer lasting VEGF blockade, and a number of studies have shown that intravitreal aflibercept is more effective than the conventional anti-VEGF agents. [17][18][19][20] If intravitreal aflibercept could penetrate the retinal surface and the entire retinal thickness to induce regression of corneal NV, [16][17][18][19] topical aflibercept administration would probably permeate and penetrate the ocular surface to induce regression of corneal NV and modulate the neovascular process.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,15,16 As VEGF plays a crucial role in the creation of corneal NV, its treatment with anti-VEGF antibodies seems to be the right method, and it has been proven in numerous studies using subconjunctival and topical anti-VEGF, such as bevacizumab and ranibizumab. 11,[18][19][20] A novel anti-VEGF, named aflibercept, has gained popularity since its approval from the Food and Drug Administration in 2011. While bevacizumab and ranibizumab use an antibody-based binding strategy, aflibercept is a fusion protein that uses 2 binding domains for VEGF receptors 1 and 2 as well as PIGF (another proposed proangiogenic factor).…”
Section: Discussionmentioning
confidence: 99%
“…5,7,[14][15][16] Other severe complications, including lens injury, macular ischemia, vitreous hemorrhage, and ocular neovascularization, were also uncommon. 5,7,[14][15][16] Although intravitreal ranibizumab and aflibercept (compared with placebo) may contribute to systemic thromboembolic events (eg, stroke and myocardial infarction), the incidence of events was as low as 1% to 2% after anti-VEGF injections 50,51 in a series of more than 8000 patients with age-related macular degeneration, which was nearly equal to the incidence of thromboembolic events in the population older than 65 years. Systemic adverse effects such as thromboembolic events and gastrointestinal bleeding were uncommon, with an incidence of 0% to 0.8% in the above anti-VEGF for RVO studies.…”
Section: Ranibizumabmentioning
confidence: 99%